The role of nanomaterials in the enhancement of non-concentrating solar collectors technology: Die Rolle von Nanomaterialien fÃ¼r die Weiterentwicklung der nicht konzentrierten Solarkollektorentechnologie - Shamshirgaran, S.R. (Wiley-VCH Verlag, 2018)
The comparison of various nanomaterialsâ effects on the performance of solar flat-plate collectors has not been drawn thoroughly in the reported literature. In this paper, modeling of a solar flat-plate collectors working with the mixture of water and different non-metallic and metallic nanomaterials has been carried out by means of MATLAB coding. A more appropriate exergy factor of solar radiation has been applied for exergy analysis; the pressure loss in collectors manifolds has been considered as well. Results show that uncommonly used cerium oxide, hybrid magnesium oxide/silver, and titanium carbide nanomaterials in flat-plate collector and commonly used ones such as copper oxide, nickel, iron, and copper have the potential to increase the heat transfer coefficient of the collector understudy. The value has been reported by the present study to be 90Â for cerium oxide case. Accordingly, an improvement in energy efficiency up to 73Â has been achieved at 4 vol.. As another outcome, the application of these nanoparticles enhances the exergy destruction within the collector. Therefore, it would be advantageous for the environment by paying attention to the environmental impacts of exergy loss. Thus, employing nanomaterial science would help to advance the solar flat-plate collector engineering technology through higher energy productivity and lower environmental destructive impacts. Â© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim